2017
DOI: 10.3390/rs9070709
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Based Sub-Pixel Change Detection Using Coarse Resolution Satellite Imagery

Abstract: Moderate Resolution Imaging Spectroradiometer (MODIS) data are effective and efficient for monitoring urban dynamics such as urban cover change and thermal anomalies, but the spatial resolution provided by MODIS data is 500 m (for most of its shorter spectral bands), which results in difficulty in detecting subtle spatial variations within a coarse pixel-especially for a fast-growing city. Given that the historical land use/cover products and satellite data at finer resolution are valuable to reflect the urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Their results showed that object detection performance improves when using SR as a pre-processing step versus the native coarser imagery. Xu et al [42] use sparse dictionary learning to generate synthetic 8× and 16× superresolved imagery from Landsat and MODIS image pairs. Their results show an increase performance for land-cover change mapping when using the super-resolved imagery.…”
Section: Super-resolution Techniques and Application To Overhead Imagerymentioning
confidence: 99%
“…Their results showed that object detection performance improves when using SR as a pre-processing step versus the native coarser imagery. Xu et al [42] use sparse dictionary learning to generate synthetic 8× and 16× superresolved imagery from Landsat and MODIS image pairs. Their results show an increase performance for land-cover change mapping when using the super-resolved imagery.…”
Section: Super-resolution Techniques and Application To Overhead Imagerymentioning
confidence: 99%
“…However, this requires abundant Landsat images (>4) (Xu et al, 2018a) that are not available in the humid tropical regions and may cause "false changes" and "inter-annual inconsistency" (Broich et al, 2011). Recently, a superresolution mapping method (Li et al, 2017;Qin et al, 2017;Xu et al, 2017) was used to reconstruct missing forest cover change 80 during 2011-2014 (Zhang et al, 2019) by fusing the PALSAR/PALSAR-2 and the MODIS normalized difference vegetation index (NDVI) with dense temporal resolution and phenological information. However, it is difficult to separate oil palm and natural forest with similar NDVI variation using such classification-based fusion.…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared their approach with STARFM and observed that the performance was better. A paper by Xu et al [151] discusses a change detection approach that uses synthetically-generated images. A sparsity-based approach is used to learn the mapping between a pair of fine and coarse images.…”
Section: Possibility Of Change Detection Using Temporally-fused Imagesmentioning
confidence: 99%